Cellular Interaction Analysis Characterizing Immunosuppressive Microenvironment Functions in MM Tumorigenesis From Precursor Stages - Liu, Zhenhao; Zhang, Siwen; Li, Hong; Guo, Jiaojiao; Wu, Dan; Zhou, Wen; Xie, Lu (Frontiers in Genetics, 2022)
Cell-Cell interaction Events (CCEs) dysregulation may relate to the heterogeneity of tumor microenvironment (TME), and would affect therapeutic responses and clinical outcomes. To reveal the alteration of immune microenvironment in bone marrow from healthy state to Multiple Myeloma (MM), scRNA-seq data of the four states including healthy state-normal bone marrow (NBM) and three disease states (MGUS, SMM, and MM) were collected for analysis. With immune microenvironment reconstruction, the cell types, including NK cells, CD8+ T cells, and CD4+ T cells, with higher percentage in disease states were associated with prognosis of MM patients. Further, CCEs were annotated and dysregulated CCEs were identified. The number of CCEs were significantly changed between disease states and NBM. The dysregulated CCEs participated in regulation of immune cell proliferation and immune response, such as MIF-TNFRSF14 interacted between early B cells and CD8+ T cells. Moreover, CCE genes related to drug response including bortezomib and melphalan provide candidate therapeutic markers for MM treatment. Further, MM patients were separated into three risk groups based on the CCE prognostic signature. Immunoregulation related differentiation and activation of CD4+ T cells corresponded to the progression status with moderate risk. These results provide a comprehensive understanding of the critical role of intercellular communication in immune microenvironment over the evolution of premalignant MM, which is related to the tumorigenesis and progression of MM, moreover suggests a way of potential target selection for clinical intervention.